Linking Fishery to Deforestation Case Study in Indonesia - Johansen, Johansen; Ariani, Mintarti; Pratono, Aluisius Hery (Yayasan Riset dan Pengembangan Intelektual, 2024)
Indonesia possesses abundant natural resources and biodiversity, especially within its fisheries industry. Despite this abundance, the nation faces challenges due to population growth and globalization, often associated with deforestation. A report from the FAO outlined various concerns regarding the correlation between forest area impacts and fish catches, considering a nursery area perspective. However, from a socio-economic standpoint, population growth consistently leads to heightened resource utilization. An inferential analysis study involving forest area, GDP, and fish catch biomass from 1990 to 2020 indicated that both forest area and GDP have a significant influence on fish catch biomass. The study revealed a consistent trend: fish catches tended to increase in the following year, but fish catch biomass showed a tendency to decrease five years later. The findings show a 99.9% coefficient of determination, suggesting a highly significant relationship. This research emphasizes the complex linkages among economic progress, forest depletion, and fishing activities, underscoring the essential role of sustainable resource management in addressing changes in both society and the environment.